Juventudes e diálogos: reflexões sobre as questões socioambientais a partir do conhecimento sociológico - Silva, Paula Herandy Costa (2023)
This academic work presents a didactic sequence carried out during the Professional Master's Degree in Teaching Sociology, in the line of research Youth and Contemporary Themes, in order to research and analyze youths from their dialogues and reflections on socio-environmental issues, when they start to study this topic in sociology classes and start to have sociological knowledge.Sociology has many important themes, among them the relationship between society and the environment, which is an important category for us to understand from classical theory to contemporary sociology with many sociological concepts. However, we can see that there is a lack of knowledge of most of the people, for associating the environment theme only with other school subjects, leaving the sociological view on this issue, in a certain disadvantage.Considering this situation, the delay with which the theme was incorporated into sociology, when we think about contemporary sociology and analyzing the books from the Programa Nacional do Livro Didático (Brazilian national textbooks program, 2018), concerned me to research, analyze and carry out a pedagogical intervention in sociology classes. In the research, the action- research method was used in the analysis of the experience of teaching sociology with a focus on socio-environmental issues, using youth dialogues and their reflections.